DESIGN AND BUILD A WEBSITE-BASED EMPLOYEE ATTENDANCE INFORMATION SYSTEM AT SATKER BEKANGDAM I/BUKIT BARISAN - Prawira Maulana Ilham; Dinih Rachmasari; Hikmatulloh Hikmatulloh (Jurnal Pilar Nusa Mandiri, 2026)
The employee attendance process at Bekangdam I/Bukit Barisan was previously conducted manually, which created potential problems such as recording errors, data loss, and delays in generating attendance reports. This study aims to design and develop a website-based employee attendance information system that supports computerized and accurate attendance recording. The system was developed using the Laravel framework as the backend, HTML and JavaScript as the frontend, and MySQL as the database management system. The system also utilizes Global Positioning System (GPS) technology to validate employee locations during the attendance process. The development method used in this research is Rapid Application Development (RAD), which consists of planning, system modeling, construction, and implementation stages. Performance testing using WAPT Pro with a simulation of 20 concurrent users for 10 minutes showed that the system successfully handled 20 user sessions with 646 pages accessed and 3,039 server request hits, with an average page response time of 0.61 seconds. Security testing using OWASP ZAP indicated that no high-risk vulnerabilities were found. In addition, User Acceptance Testing (UAT) involving 20 respondents showed that the system functions according to user needs. The results indicate that the developed system improves attendance recording accuracy, accelerates attendance reporting, and increases the effectiveness of employee attendance management.